2012
DOI: 10.1159/000339440
|View full text |Cite
|
Sign up to set email alerts
|

Early Arterial Stiffness and Inflammatory Bio-Markers in Normotensive Polycystic Kidney Disease Patients

Abstract: Background/Aims: Cardiovascular disease is the main cause of morbidity and mortality in autosomal-dominant polycystic kidney disease (ADPKD) patients. To clarify temporal relationship between ADPKD, hypertension and the loss of renal function, we examined these factors in patients with early-stage ADPKD who did not yet have hypertension. Methods: Fifty patients with ADPKD (42% males, 36.6 ± 9.9 years, no blood pressure medication) and 50 healthy controls (44% males, 35.4 ± 6.4 years) were studied cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 60 publications
1
32
0
6
Order By: Relevance
“…Arterial stiffness has been positively associated with levels of different systemic inflammatory markers in healthy individuals [9] and different patient populations [10,11]. One COPD study showed weak correlations with interleukin (IL)-6 and soluble tumour necrosis factor receptor 1 (sTNFR1), but not with sTNFR2 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Arterial stiffness has been positively associated with levels of different systemic inflammatory markers in healthy individuals [9] and different patient populations [10,11]. One COPD study showed weak correlations with interleukin (IL)-6 and soluble tumour necrosis factor receptor 1 (sTNFR1), but not with sTNFR2 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Early vascular changes and endothelial dysfunction have been shown in ADPKD patients in our previous studies [8,13]. Moreover, endothelium-dependent relaxation is impaired and endothelial synthase activity is decreased in this population [14,15].…”
Section: Introductionmentioning
confidence: 75%
“…Although the activation of systemic RAS due to local cyst pressure on the renal vasculature has been a widely accepted hypothesis with regard to the development of hypertension in ADPKD, the evidence of early vascular changes and endothelial dysfunction in normotensive ADPKD patients showed the necessity of further studies in this area [5,13,14,15]. Furthermore, recent studies have shown that intrarenal RAS activation, hyperuricemia, impaired nitric oxide generation, inflammation, and increased oxidative stress could be associated with the development of hypertension in ADPKD patients [8,9,13,15,23]. In addition, genetic predisposition might be related to early occurrence of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise mechanism of hypertension in early ADPKD has not yet been elucidated, early vascular changes have been shown in normotensive ADPKD patients prior to the development of hypertension [28]. Recently, we demonstrated arterial stiffness and inflammation in normotensive ADPKD patients with preserved kidney function that might be a contributing factor for early onset of hypertension [29]. Nevertheless, the pathogenesis of hypertension in ADPKD and the trigger factor remains unclear.…”
Section: Discussionmentioning
confidence: 99%